“Please Don’t Take Our Ghost Away!”: Ontario’s Haunted Roads - Demeter, Susan (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
Ghost roads have a special place in our cultural imagination. They are often lonely stretches of county highways or backroad locales with haunted histories that speak of tragic death, mysterious lights, and ghostly visitations. These roads are often sites of pilgrimage for thrill seekers and paranormal enthusiasts, who in turn add to the lore of these roads. This article explores the paranormal history of three Ontario Ghost Roads—Mississauga’s Trail, Texas Road, and Buck Hill Road—through the author’s firsthand observations and research of primary and secondary sources. What draws us to our haunted roads and what may this reveal about us and our relationship to each other and the natural and unseen world?